Investigating Eleventh-Grade Students' Perceptions of Quizizz's Efficacy in Developing English Reading Comprehension at MAN 2 Kota Bengkulu - Malia, Viska; Zasrianita, Fera; Serasi, Reko (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study investigates eleventh-grade students’ perceptions of Quizizz in developing English reading comprehension at MAN 2 Kota Bengkulu. Using an explanatory sequential mixed-method design, quantitative data were collected through questionnaires and qualitative insights through interviews. Results show students perceive Quizizz as engaging, easy to use, and motivating. The platform improves comprehension, vocabulary, and focus, although challenges include unstable internet and time pressure. Overall, Quizizz is considered effective in enhancing EFL reading comprehension.